Determination of Sales Growth Factors and Growth of Total Assets to Price to Book Value - I Wayan Budi Artha (Journal of Accounting and Finance Management, 2023)
Research Article Determination of Sales Growth Factors and Growth of Total Assets to Price to Book Value is a scientific article of literature study within the scope of Financial Management science. The purpose of this article is to establish a hypothesis of influence between variables that will be used in further research. Research objects are sourced from online libraries, google scholar, mendeley and other academic online media. Literature research methods, starting from e-books and open access e-journals and reviewing previous research related to this research. The results of this study are: 1) Sales Growth affects Price to Book Value; 2) The growth of Total Assets affects the Price to Book Value; and 3) Sales Growth affects Total Asset Growth.